Managing risks in information technology projects - NEO, Boon Siong (Institutional Knowledge at Singapore Management University, 1994)
The development and implementation of IT (Information Technology) projects are plagued with problems of cost and time overruns. technical inadequacy, inability to meet user requirements. lack of utilization. and failure to achieve anticipated beneﬁts. These problems occur to some projects and not to others because I) IT projects have different profiles of risk. and 2) IT project risks have been managed more or less effectively. This paper synthesizes the literature into four classes of risks. and applies it to evaluate TradeNet. an EDLbased trading system implemented in Singapore in I989. Through a case study of TradeNet. we derived a typology of four risk management strategies for IT projects: I) risk preemption. 2) risk reduction. 3) risk isolation. and 4) risk sharing. Each risk management strategy is described in terms of the tactics and mechanisms used in the TradeNet project. Some of these tactics include: positioning the system. providing incentives for adoption. managing project development. information and expertise. scoping the system. separating accountability. surfacing of problems. cooperating with organizations, coopting key personnel. and connecting to other systems. The relevance of these risk management strategies is analyzed and discussed.